Journalism Research and the Hierarchy of Influences Model: A Global Perspective - Reese, Stephen D. (Brazilian journalism research, 2007)
My emphasis in this article is on international and global approaches to journalism research. And my challenge is to consider some integrative and global contexts for that task. I have always advocated setting up clear conceptual levels of analysis in examining media questions within the emerging communication subfeld in the U.S. of media sociology. The work of my colleague Pam Shoemaker and me began with this idea to consider the various levels of infuence of shaping media content (SHOEMAKER & REESE, 1996). I took this a step further in approaching similar questions of relevance to “global journalism” (REESE, 2001) and continue to be interested in those issues.